Parental employment in families with disabilities: assessment, factors, solutions - Pritvorova, T.P.; Atabayeva, A.K.; Petrenko, Ye.S. (KU Publ., 2021)
Object: Purpose of this paper is to assess the factors affecting the ability of a parent with a disabled child to find employment to develop approaches to addressing this issue, including in the framework of the Employment Center activities. Methods: This study includes a sociological survey conducted in 5 regions (300 families) of Kazakhstan, processing of the results using structural analysis and SmartPLS statistical methods. Results: According to the results of a sociological survey, the share of working mothers after the birth of a child with special needs is found to be decreasing from 86 % to 42 %. Of the 58 % of those unemployed, 31 % would like to realize their human potential and increase family income. A PLS-PM model processing of the survey results allowed to identify significant factors: time spent on childcare, his diagnosis, and family income. Authors of the article have affirmed two hypotheses about the relationship between mother’s status and the family income with the mother’s willingness to find employment, mainly in the form of partial or temporary one. They have also confirmed the hypothesis about the influence of “Additional government free of charge family services” on the mother’s ability to work. A significant number of respondents expressed a desire for government support to provide employment opportunities in a form accessible to the parent and additional income. This led to the conclusion that the Employment Centers are not working effectively enough with this category of citizens. In this regard, for Employment Centers, the authors propose three algorithms of actions for the employment of this social group, which maximizes the range of possible solutions for each individual case. Conclusions: Realization of the human potential of parents with a disabled child is related to their employment and labor income. Employment Centers need to take an active position on the issue of employment of target groups by introducing a profiling methodology and fixing the specialization of specific employees on groups with social issues for targeted individual work with each case. We suggest the possibility of addressing the issue within the framework of social entrepreneurship.
Мүмкіндігі шектеулі отбасыларда ата-аналардың жұмысқа орналасуы: бағалау, факторлар, шешімдер
Занятость родителя в семьях с ограниченными возможностями: оценка, факторы, решения
Keywords: families with disabilities; parental employment; PLS analysis; employment algorithms